E-Health Strategies Worldwide - Lorenzi, N. M. (Yearbook of Medical Informatics, 2005)
Healthcare worldwide is in a state of constant change. The multitude of changes require creative solutions that range from restructuring healthcare to provide better services to the effective use of information technology (e-health). Both are daunting tasks in any individual organization let alone on a national or international level. To completely cover the many e-health initiatives worldwide would require a more comprehensive document than is possible within this article. Therefore, this article represents a sample of the e-health efforts that are occurring simaltenously throughout the world.